Cell Dimension and Proportion of Acacia aulacocarpa Wood in Axial and Radial Directions from Gunung Kidul, Yogyakarta - Viola Elizabeth; Fanny Hidayati (Jurnal Ilmu Pertanian Indonesia, 2025)
The information related anatomical characteristics (cell dimension and proportion) of Acacia aulacocarpa is still limited also for its axial and radial variations. This research aimed to analyze variation of the anatomical characteristics in axial and radial direction. Three trees of 27-year-old A. aulacocarpa planted in Gunung Kidul Yogyakarta were used. This research covered a completely randomized design with two factors, the axial direction (base, middle, and top of the trunk) and the radial direction (near pith, between pith and bark, and near bark) in triplicate. A two-way analysis of variants was used. The measured parameters were fiber dimensions (length, diameter, lumen diameter, and wall thickness) and cell proportions (fiber, vessel, ray parenchyma, and axial parenchyma). The results showed that average value of fiber dimensions was as follow: fiber length 0.94 mm; fiber diameter 17.43 µm; lumen diameter 11.75 µm; and fiber wall thickness 2.84 µm. The average value of cell proportions was 52.48% of fibers cell proportion; 17.5% of wood vessel proportion; 15.69% of axial parenchyma proportion; and 16.68% of ray’s parenchyma proportion. The axial position factor does not affect the proportion and dimensions of the fiber. However, the radial position factor affects the proportion of fiber cells, the proportion of wood vessels, the proportion of axial parenchyma, fiber length, lumen diameter, and fiber wall thickness. Fiber length, fiber lumen diameter, cell wall thickness increased from near the pith to the middle and then remained relatively constant toward the bark. Based on these results, it is suspected that the middle and near the bark are mature wood. Keywords: Acacia aulacocarpa, cell dimension, cell proportion, radial direction, axial direction